2018
DOI: 10.1177/0891243218763313
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Masculinity and Young Men’s Circumscribed Engagement in Contraceptive Management

Abstract: This research explores how gender shapes contraceptive management through in-depth interviews with 40 men and women of color ages 15 to 24, a life stage when the risk of unintended pregnancy is high in the United States. Although past research focuses on men’s contraception-avoidant behaviors, little sociological work has explored ways men engage in contraception outside of condoms, such as contraceptive pills. Research often highlights how women manage these methods alone. Our research identifies how young me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…This article makes both empirical and theoretical contributions. First, with few exceptions, little work has explored young men's approaches to pregnancy prevention and resolution methods besides condoms (Fefferman and Upadhyay 2018). Our research speaks to this by focusing on men's views of condoms as well as other methods.…”
Section: Resultsmentioning
confidence: 99%
“…This article makes both empirical and theoretical contributions. First, with few exceptions, little work has explored young men's approaches to pregnancy prevention and resolution methods besides condoms (Fefferman and Upadhyay 2018). Our research speaks to this by focusing on men's views of condoms as well as other methods.…”
Section: Resultsmentioning
confidence: 99%
“…College men may not perceive themselves at risk for HPV or HPV-related complications. Studies have indicated that college men are more concerned about pregnancy prevention than STI prevention, therefore both supporting and giving responsibility to women in their use of female contraception ( Breny & Lombardi, 2017 ; Fefferman & Upadhyay, 2018 ). Considering that HPV-related cancers are slow growing, the messaging to adolescent and young men may need to focus more on the prevention of genital warts instead.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ier portrayed in Figures 4a-4b openly advised a pregnant woman to protect her dwelling against the mosquito. The Brazilian communication situated women as competently dealing with pregnancy and caring during the Zika epidemics while the male remained detached from caring and parenting responsibilities (60). Across all material studied, we did not discover a single piece speaking directly to men.…”
Section: Resultsmentioning
confidence: 69%
“…Advantaged women did not reveal complications associated with contraception management. Nevertheless, some participants acknowledged men did not like condoms, so women had resort to other methods (5,30,34,(58)(59)(60)63):…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation